Reset - Bagge, Peter 1957- (Dark Horse, 2013)
f you could relive major events in your life, would you take a stab at making things better-and would your best attempts only make things worse? Or would you use your second chance to put your most twisted, perverted fantasies in motion? These are questions washed up actor and comedian Guy Krause asks himself after he signs up to be the main research subject for a virtual reality experiment! This new hardcover graphic novel from Harvey Award-winning writer/artist Peter Bagge--creator of Hate and Apocalypse Nerd--collects the hilarious, offbeat Reset comic-book series in its entirety
Keywords: Bagge, Peter -- 1957-; Graphic novels; Underground comics; Virtual reality -- Comic books, strips, etc; Comic